Baseline characteristics, management, and predictors of early mortality in cardiogenic shock: insights from the FRENSHOCK registry. (31st December 2021) - Delmas, Clement; Roubille, François; Lamblin, Nicolas; Bonello, Laurent; Leurent, Guillaume; Levy, Bruno; Elbaz, Meyer; Danchin, Nicolas; Champion, Sebastien; Lim, Pascal; Schneider, Francis; Cariou, Alain; et al.
Abstract: Aims: Published data on cardiogenic shock (CS) are scarce and are mostly focused on small registries of selected populations. The aim of this study was to examine the current CS picture and define the independent correlates of 30 day mortality in a large non‐selected cohort. Methods and results: FRENSHOCK is a prospective multicentre observational survey conducted in metropolitan French intensive care units and intensive cardiac care units between April and October 2016. There were 772 patients enrolled (mean age 65.7 ± 14.9 years; 71.5% male). Of these patients, 280 (36.3%) had ischaemic CS. Organ replacement therapies (respiratory support, circulatory support or renal replacement therapy) were used in 58.3% of patients. Mortality at 30 days was 26.0% in the overall population (16.7% to 48.0% depending on the main cause and first place of admission). Multivariate analysis showed that six independent factors were associated with a higher 30 day mortality: age [per year, odds ratio (OR) 1.06, 95% confidence interval (CI): 1.04–1.08], diuretics (OR 1.74, 95% CI: 1.05–2.88), circulatory support (OR 1.92, 95% CI: 1.12–3.29), left ventricular ejection fraction <30% (OR 2.15, 95% CI: 1.40–3.29), norepinephrine (OR 2.55, 95% CI: 1.69–3.84), and renal replacement therapy (OR 2.72, 95% CI: 1.65–4‐49). Conclusions: Non‐ischaemic CS accounted for more than 60% of all cases of CS. CS is still associated with significant but variable short‐term mortality according to the cause and first place of admission, despite frequent use of haemodynamic support, and organ replacement therapies.